Relationship between Trait Emotional Intelligence, Narcissism, and Life Satisfaction - Neha (My University, 2023)
This study examined the relationship between trait emotional intelligence, narcissism, and life satisfaction. The sample consisted of 153 participants ranging from 18-30 years. The data was collected using Trait Emotional Intelligence Questionnaire (TEIQue-SF), Satisfaction with Life Scale, and Narcissistic Personality Inventory (NPI-16). Results support both hypotheses that emotional intelligence positively correlates with narcissism and life satisfaction. Pearson correlation showed that trait emotional intelligence, narcissism, and life satisfaction are significantly correlated at a 0.01 level. Further regression analysis shows a total of 4.2 variance in narcissism was explained by trait emotional intelligence, and 16.4 variance in life satisfaction was explained by trait emotional intelligence. The findings of this study provide evidence that Trait emotional intelligence positively impacts narcissism and life satisfaction. Implications and directions for further research are discussed.
Keywords: Emotional intelligence; Trait emotional intelligence; Narcissism; Life satisfaction